2019
DOI: 10.1038/s41598-019-45064-8
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the significance of the dive response during voluntary surface apneas in the bottlenose dolphin, Tursiops truncatus

Abstract: The dive response is well documented for marine mammals, and includes a significant reduction in heart rate ( f H ) during submersion as compared while breathing at the surface. In the current study we assessed the influence of the Respiratory Sinus Arrhythmia (RSA) while estimating the resting f H while breathing. Using transthoracic echocardiography we measured f H , and stroke volume (SV) during volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 55 publications
7
56
0
Order By: Relevance
“…S1). Here, we investigated the drivers of these modes, which are ascribed to both the dive response and RSA (Fahlman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…S1). Here, we investigated the drivers of these modes, which are ascribed to both the dive response and RSA (Fahlman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Development of electronic devices that could record physiological changes continuously allowed the cardiovascular responses to be measured in freely diving birds and mammals. These studies confirmed that a diving bradycardia was observed during voluntary dives, but it was much more variable and not always as extreme as during forced dives (Elsner, 1965(Elsner, , 1966Elsner et al, 1966;Kooyman and Campbell, 1972;Jones et al, 1973;Butler and Woakes, 1979;Kanwisher et al, 1981;Blix and Kjekshus, 1983;Blix, 1987;Ponganis et al, 1991;Thompson and Fedak, 1993;Andrews et al, 1997;Ponganis et al, 1997;Houser et al, 2010;Fahlman et al, 2019b). Based on these data, the significance of the dive response has been argued.…”
Section: Introductionmentioning
confidence: 52%
“…The pre-dive f H was the average f H 60 s before the breath-hold (Pre). As past studies in the bottlenose dolphin have shown that f H , stroke volume, and cardiac output decreases with longer dive duration (Fahlman et al, 2019b), the minimum instantaneous f H (if Hmin ) during the breath-hold, and the average instantaneous f H (if Hend ) over the last 10 s of the breath-hold, were evaluated and expected to be lower for longer dives. To assess the anticipatory, or conditioned response, we compared the rate of change in instantaneous f H (dif H /dt), the average instantaneous f H (if Hstart ), and the minimum instantaneous f H (if Hstartmin ) during the first 20 s of the breath-hold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations